2002
DOI: 10.2337/diabetes.51.12.3391
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 Induces Cellular Insulin Resistance in Hepatocytes

Abstract: Interleukin (IL)-6 is one of several proinflammatory cytokines that have been associated with insulin resistance and type 2 diabetes. A two-to threefold elevation of circulating IL-6 has been observed in these conditions. Nonetheless, little evidence supports a direct role for IL-6 in mediating insulin resistance. Here, we present data that IL-6 can inhibit insulin receptor (IR) signal transduction and insulin action in both primary mouse hepatocytes and the human hepatocarcinoma cell line, HepG2. This inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
565
4
31

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 763 publications
(624 citation statements)
references
References 56 publications
24
565
4
31
Order By: Relevance
“…Thus, lowgrade inflammation seems to be a key finding of diabetic nephropathy, and could even be the reason for the reduced insulin sensitivity in these patients. Such a view is supported by experimental data showing that IL-6 is capable of inducing insulin resistance in mouse hepatocytes and human hepatocarcinoma cell lines by affecting both proximal and distal events in hepatic insulin receptor signal transduction [24].…”
Section: Discussionmentioning
confidence: 85%
“…Thus, lowgrade inflammation seems to be a key finding of diabetic nephropathy, and could even be the reason for the reduced insulin sensitivity in these patients. Such a view is supported by experimental data showing that IL-6 is capable of inducing insulin resistance in mouse hepatocytes and human hepatocarcinoma cell lines by affecting both proximal and distal events in hepatic insulin receptor signal transduction [24].…”
Section: Discussionmentioning
confidence: 85%
“…While the role of IL-6 in whole-body insulin resistance is unclear, it is generally accepted that excessive circulating IL-6 causes hepatic insulin resistance [30]. This conclusion is based on several observations demonstrating that exogenous administration of IL-6 impairs insulin signal transduction in the liver in vitro [36,37] and in vivo [13]. In addition, IL-6-neutralising antibodies have been shown to reverse hepatic insulin resistance in mice [38,39], while transient overproduction of IL-6 in skeletal muscle by in vivo electroporation resulted in liver inflammation [40].…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, the role of IL-6 in whole body energy homeostasis remains partly contradictory. However, several experimental studies have shown that IL-6 impairs insulin sensitivity and action in rodent and human hepatocytes as well as inducing hepatic insulin resistance in vivo in mice [48][49][50]. This insulin desensitising effect in liver cells is, in part, the result of IL-6 inducing marked inflammation in this tissue [29].…”
Section: Discussionmentioning
confidence: 99%